2015
DOI: 10.1186/s12917-015-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adequacy of essential nutrient intake in obese dogs undergoing energy restriction for weight loss: a cohort study

Abstract: BackgroundCanine obesity is usually treated with dietary energy restriction, but data are limited regarding nutritional adequacy. The aim of the current study was to compare intake of essential nutrients with National Research Council recommendations in obese dogs during weight management with a purpose-formulated diet.MethodsTwenty-seven dogs were included in this non-randomised retrospective observational cohort study. All were determined to be systemically well, and without significant abnormalities based u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 24 publications
5
25
1
4
Order By: Relevance
“…Two further in vivo studies showed a lack of clinical signs when participants were fed purpose-formulated weight management diets in a clinical setting. 20,21 These findings cannot be extrapolated to show that all veterinary therapeutic weight loss diets will not cause deficiency, but it suggests that there may be less inherent risk for nutrient deficiency with a purposeformulated diet for weight loss as opposed to feeding less of an adult maintenance diet. The optimal micronutrient profile for weight management is still unknown, although recent American Animal Hospital Association (AAHA) Weight Management Guidelines recommend consulting a board-certified veterinary nutritionist for cases that require fewer than 60% of resting energy requirements for ideal weight to ensure adequate diet formulation.…”
Section: Micronutrientsmentioning
confidence: 81%
“…Two further in vivo studies showed a lack of clinical signs when participants were fed purpose-formulated weight management diets in a clinical setting. 20,21 These findings cannot be extrapolated to show that all veterinary therapeutic weight loss diets will not cause deficiency, but it suggests that there may be less inherent risk for nutrient deficiency with a purposeformulated diet for weight loss as opposed to feeding less of an adult maintenance diet. The optimal micronutrient profile for weight management is still unknown, although recent American Animal Hospital Association (AAHA) Weight Management Guidelines recommend consulting a board-certified veterinary nutritionist for cases that require fewer than 60% of resting energy requirements for ideal weight to ensure adequate diet formulation.…”
Section: Micronutrientsmentioning
confidence: 81%
“…De acordo com a literatura científica especializada, a taxa média semanal de perda de peso corporal em cães domiciliados e manejados pelos seus proprietários é de em média 0,7%; sendo assim, para a perda de 20% do peso corporal são necessários no mínimo de 6 a 7 meses (CARCIOFI et al, 2005;GERMAN et al, 2007;GERMAN et al, 2009;BRUNETTO, 2010;GERMAN et al, 2015a;GERMAN et al, 2015b, TVARIJONAVICIUTE et al, 2013.…”
Section: Ecocardiograma (Eco)unclassified
“…A duração do programa de perda de peso, assim como a taxa de perda de peso semanal observados foram semelhantes à de outros estudos, que também avaliaram cães de tutores (CARCIOFI et al, 2005;GERMAN et al, 2007;GERMAN et al, 2009;BRUNETTO, 2010;GERMAN et al, 2015a;GERMAN et al,2015b, TVARIJONAVICIUTE et al, 2013 (GERMAN et al, 2007;GERMAN et al, 2015a;TVARIJONAVICIUTE et al, 2013;GERMAN, 2016b). A redução da massa gorda, aliada ao aumento da % de massa magra, é considerada um bom resultado.…”
Section: Correlaçõesunclassified
See 2 more Smart Citations